Subjective health complaints in early adolescence reflect stress: A study among adolescents in Western Sweden. Issue 4 (June 2022) - Corell, Maria; Friberg, Peter; Löfstedt, Petra; Petzold, Max; Chen, Yun
Aims: Mental health problems are common among Swedish adolescents and are sometimes referred to as 'stress-related'. The overall aim of this study is to do an analysis of subjective health complaints (SHCs) and perceived general stress among adolescents in Sweden, both their prevalence and association, by gender, migration background, family structure and socioeconomic conditions. Methods: Data from the baseline (comprising 2283 adolescents aged 13) of the STudy of Adolescence Resilience and Stress (STARS) study in Västra Götaland in Sweden were used. SHCs were measured by the Psychosomatic Problems Scale (PSP-scale) and self-reported stress was measured by Cohen's Perceived Stress Scale (PSS-10). Socioeconomic conditions were measured with the Family Affluence Scale (FAS) and the MacArthur Scale of Subjective Social Status (SSS). Statistical analyses included Student's t -tests and ANOVAs of means, linear and logistic regression analyses and Pearson's correlations. Results: Social inequalities in both SHCs and self-reported stress were found; levels were higher among girls, adolescents living with one parent or in families with less favourable socioeconomic conditions. Self-reported stress and SHCs were found to be strongly correlated ( r =0.70). Correlations with self-reported stress were stronger for psychological complaints ( r =0.71) than for somatic complaints ( r =0.52). Correlations did not vary with socioeconomic conditions of the family. Conclusions: SHCs do reflect general stress among adolescents, and it is appropriate to address the complaints as 'stress-related'. Measures to improve adolescents' mental health by reducing levels of SHCs should pay special attention to stressors in adolescents' daily lives and strengthening adolescent's coping resources and strategies.